2008
DOI: 10.1165/rcmb.2007-0204oc
|View full text |Cite
|
Sign up to set email alerts
|

Combustion-Derived Hydrocarbons Localize to Lipid Droplets in Respiratory Cells

Abstract: Combustion-generated radicals interact to form polynuclear aromatic hydrocarbons (PAHs), including carcinogens. PAHs aggregate into 20- to 50-nm particles, which extend into branched-chain structures (soots). Incomplete combustion yields black soot particles and black smoke. Many PAHs, including those in soots, fluoresce upon excitation. We have reported that butadiene soot (BDS), generated during combustion of the high-volume petrochemical 1,3-butadiene, serves as a reproducible example of combustion-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 48 publications
1
38
1
Order By: Relevance
“…To determine the localization of B[a]P in lysosomes of Hepa1c1c7 cells LysoTracker ¾ was used (see Figure 9). Although it was reported earlier that there is [18,19] no significant accumulation of B[a]P in lysosomes of Clone 9 cells and BEAS-2B cells respectively, our results show substantial colocalization of B[a]P fluorescence with the lysosomal fluorescence in Hepa1c1c7 cells.…”
Section: Lysosomescontrasting
confidence: 90%
See 2 more Smart Citations
“…To determine the localization of B[a]P in lysosomes of Hepa1c1c7 cells LysoTracker ¾ was used (see Figure 9). Although it was reported earlier that there is [18,19] no significant accumulation of B[a]P in lysosomes of Clone 9 cells and BEAS-2B cells respectively, our results show substantial colocalization of B[a]P fluorescence with the lysosomal fluorescence in Hepa1c1c7 cells.…”
Section: Lysosomescontrasting
confidence: 90%
“…Stored contaminants might get released in the cell cytoplasm at a later time point in a controlled manner to prevent any immediate damage to cellular processes due to their toxic nature. Miller and Whitlock showed [18] that two thirds of the original B[a]P recovered adhered supposedly to LDs in lung cells more than 5 months after exposure.…”
Section: Lipid Droplets (Lds)mentioning
confidence: 99%
See 1 more Smart Citation
“…BDS is rich in particles that can absorb PAHs. Microarray analysis of human bronchoepithelial cells (BEAS-2B) exposed to BDS showed upregulation of Nrf2-associated genes (Murphy et al 2008). The authors suggested that an increase in cellular oxidative stress was the result of exposure to BDS.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Subsequent to exposure, PAHs cross through cell membranes and being lipophilic, undergo intracellular accumulation by concentrating in lipid droplets [5]. Studies from our research group have shown that PAHs through a & A.…”
Section: Introductionmentioning
confidence: 99%